The AiiDA-Spirit Plugin for Automated Spin-Dynamics Simulations and Multi-Scale Modeling Based on First-Principles Calculations - Rüßmann, Philipp; Ribas Sobreviela, Jordi; Sallermann, Moritz; Hoffmann, Markus; Rhiem, Florian; Blügel, Stefan (Frontiers in Materials, 2022)
Landau-Lifshitz-Gilbert spin-dynamics calculations based on the extended Heisenberg Hamiltonian is an important tool in computational materials science involving magnetic materials. In this work we present the AiiDA-Spirit Python plugin that connects the spin-dynamics code Spirit to the AiiDA framework. AiiDA provides a Python interface that facilitates performing high-throughput calculations while keeping track of the data provenance between calculations in a directed acyclic graph. The AiiDA-Spirit interface thus provides an easy way for high-throughput spin-dynamics calculations. The interface to the AiiDA infrastructure furthermore has the advantage that input parameters for the extended Heisenberg model can be extracted from high-throughput first-principles calculations including a proper treatment of the data provenance that ensures reproducibility of the calculation results. We describe the layout of the AiiDA-Spirit plugin and demonstrate its capabilities. The features of the plugin are showcased using selected examples for Landau-Lifshitz-Gilbert spin-dynamics and Monte Carlo calculations. Furthermore, the integration with first-principles calculations through AiiDA for $γ$--Fe, where the spin-spiral ground state is investigated for varying lattice constants, is demonstrated.